THE MECHANISMS OF Cl3– - CENTERS AT CRYSTALS KCl BY LOWING THE SYMMETRY OF THE GRATING BY THE CATION-HOMOLOGS AND BY PLASTIC AND ELASTIC DEFORMATION - Aitmagambetova, Z.; Bizhanova, K.; Shunkeev, K. (Recent Contributions to Physics, 2018)
At work by the method of absorbtional spectroscopy were investigate the effectivenesses of creating x-ray radiation of Cl3–- centers at crystals KCl in the field of cation-homologs. The stripe of absorption in the area of the specter of absorption which is characterize for ion of halogen – (Cli–) which is in the structure of (Cli–)acaLii+ (Cli–), (Cl3–)acaNai+Cli– and (Cl3–)aca+Src+Cli–- centers at crystals KCl-Li, KCl-Na и KCl-Sr were registered at the first time.